Behavioral responses of three armadillo species (Mammalia: Xenarthra) to an environmental enrichment program in Villavicencio, Colombia - Cortés Duarte, Alexandra; Trujillo, Fernando; Superina, Mariella (Zoo biology, 2016)
Enrichment is a powerful tool to improve the welfare of animals under human care. Stress‐related health and behavioral problems, as well as reproductive failure, are frequent in armadillos (Xenarthra, Cingulata, Dasypodidae) under human care, which hinders the development of successful ex situ conservation programs. Nevertheless, scientific studies on the effect of enrichment programs on armadillos are virtually non‐existent. The objective of this study was to assess the impact of an enrichment program on the behavior of armadillos under human care. The behavior of 12 individuals of three species (Dasypus novemcinctus, D. sabanicola, and Cabassous unicinctus) maintained at Finca El Turpial, Villavicencio, Colombia, was recorded using scan sampling during three daily time blocks of 2 hr each before (4 weeks) and after (4 weeks) implementing an enrichment program. Enrichment did not stimulate the armadillos to change or extend their activity period. In general, activity levels were low during the entire study, and virtually no activity was recorded in the morning in any species, neither without nor with enrichment. The latter did, however, improve welfare by reducing abnormal and increasing natural foraging behaviors. All species were attracted by artificial termite mounds. Dasypus spp. showed special interest in cardboard boxes with food, while Cabassous was mainly attracted to hollow plastic balls filled with food. Our results suggest that separate enrichment programs need to be developed for different armadillo species, and that they should be applied during the time of day at which they are most active. Zoo Biol. 35:304–312, 2016. © 2016 Wiley Periodicals, Inc.